Esophageal perforation secondary to malignant gastric outlet obstruction: a case report - Johnson, Helen M.; Anciano, Carlos J.; Laks, Shachar (My University, 2019)
Background Esophageal perforation is a rare presenting sign of gastric cancer. To date, only nine case reports of this phenomenon have been previously published. Case presentation Esophageal perforation was diagnosed radiographically during workup for acute chest pain in a 67-year-old man. Emergent endoscopy confirmed esophageal perforation and biopsied a pre-pyloric mass confirmed to be adenocarcinoma. The perforation was managed with endoscopically placed transluminal pleural and mediastinal drains and esophageal stenting. The gastric outlet obstruction was temporized with a transpyloric stent. After the patient recovered from sepsis, distal gastrectomy was performed and he made a full recovery. Conclusions Rarely, pre-pyloric gastric cancer can present with Boerhaave syndrome, spontaneous esophageal perforation associated with forceful vomiting. We present the tenth report in the literature of this phenomenon and the first to be initially treated with endoscopic stenting and transluminal thoracoscopic drainage. When endoscopic management is used to treat patients with Boerhaave syndrome, it may be beneficial to examine the entire stomach to evaluate for malignant etiology.